Effects of core stabilization exercises with and without dry cupping on pain and disability in patients with sacroiliac joint dysfunction - Ain, Noor Ul; Bashir, Muhammad Salman; Noor, Rabiya; Ikram, Mehwish; Iftikhar, Ayesha; Najm, Rabiah (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the impact of core stabilisation exercises with and without dry cupping on aches and impairment in sacroiliac joint dysfunction. Method: The randomised controlled trial was conducted from June 15, 2022, to November 30, 2023, at the Riphah Rehabilitation Centre, Lahore, Pakistan, and comprised subjects who were randomised into two groups. Intervention Group A received core stabilisation training in addition to dry cupping therapy, while control Group B received core stabilisation training alone. The intervention was done once a week for 6 weeks. Numeric Pain Rating Scale and Modified Oswestry Disability Index were used to assess pain and disability outcomes, respectively, at the baseline and post-intervention. Data was analysed using SPSS 25. Results: Of the 28 patients, 12(42.9%) male and 16(57.1%) female with mean age 29.86±3.30 were in Group A, and the remaining 14(50%) with mean age 31.21±3.45 were in Group B (p>0.05). Post-intervention, both groups showed significant improvement (p<0.05) compared to baseline values, but Group A values were significantly better than Group B values (p<0.05). Conclusion: Dry cupping therapy with core stabilisation exercise was more effective in reducing pain and improving disability in patients with sacroiliac joint dysfunction than core stabilisation exercise alone. RCT registration Number: ClinicalTrials.govt with ID: NCT05404984. Key Words: Dry cupping, Core strengthening exercises, Sacroiliac joint dysfunction.